The Fedderate Charter and its implications for the thirteenth-century social and economic landscapes of North-east Scotland. (3rd July 2021) - Shepherd, Colin
ABSTRACT: The late twelfth–early thirteenth-century Fedderate Charter gives a unique view of aspects of the thirteenth-century landscape of North-east Scotland that is not available from other sources. It is a multi-purpose document shedding light on agricultural, economic and social change, landscape and place-name development, secular religious observance and routeways. The method employed to describe the boundary of the estate is also unusual and may relate to the size of the grant and customary methods of witnessing such events.